2023
DOI: 10.1101/2023.02.20.529285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased actin binding is a shared molecular consequence of numerous spinocerebellar ataxia mutations in β-III-spectrin

Abstract: Spinocerebellar ataxia type 5 (SCA5) is a neurodegenerative disease caused by mutations in the SPTBN2 gene encoding the cytoskeletal protein β-III-spectrin. Previously, we demonstrated that a L253P missense mutation, localizing to the β-III-spectrin actin-binding domain (ABD), causes increased actin-binding affinity. Here we investigate the molecular consequences of nine additional ABD-localized, SCA5 missense mutations: V58M, K61E, T62I, K65E, F160C, D255G, T271I, Y272H, and H278R. We show that all of the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The previously characterized A119T ABD also lacked the N-terminal 18 residues; we previously showed that N-terminal residues preceding CH1 impact the stability of the related ABD of β-III-spectrin [27]. Interestingly, loss of cooperative unfolding was not observed for any of ten different missense variants in the related ABD of β-III-spectrin [35]. Most of the β-III-spectrin variants localized to the CH1/CH2 interface, including L253P and T271I, which are at the equivalent residue positions as α-actinin-2 M228T and T247M, respectively.…”
Section: Human α-Actinin-2 Cardiomyopathy Missense Variants Attain Fo...mentioning
confidence: 91%
“…The previously characterized A119T ABD also lacked the N-terminal 18 residues; we previously showed that N-terminal residues preceding CH1 impact the stability of the related ABD of β-III-spectrin [27]. Interestingly, loss of cooperative unfolding was not observed for any of ten different missense variants in the related ABD of β-III-spectrin [35]. Most of the β-III-spectrin variants localized to the CH1/CH2 interface, including L253P and T271I, which are at the equivalent residue positions as α-actinin-2 M228T and T247M, respectively.…”
Section: Human α-Actinin-2 Cardiomyopathy Missense Variants Attain Fo...mentioning
confidence: 91%